Valuing Simplicity: Developing a Good Point of Care Diagnostic - Engel, Nora; Krumeich, Anja (Frontiers in Sociology, 2020)
Point-of-care testing promises laboratory-based precision in settings that do not have easy access to laboratories or where processing tests takes too long or is too costly. Developers and global health actors stress values and norms such as simplicity, rapidity and accuracy for realizing diagnostic innovations that work at point of care and are aligned to the specific requirements of point-of-care settings. This paper uses fieldwork among diagnostic manufacturers, scientists, donors, members of civil society, industry consultants, international organizations, regulators, policymakers, programme officers, lab technicians, and clinicians involved in development and implementation of tuberculosis and HIV diagnostics, to examine how norms and values of what constitutes a good point-of-care diagnostic are operating in practice through both top-down and bottom-up dynamics. It draws the link between design, evidence and adoption of diagnostics and how the different actors interpret the values underpinning the new practice. The analysis draws on literature on valuation practices, evidence-making and technology design in science and technology studies and medical sociology. The findings reveal how these values constitute innovation, implementation, and evaluation practices across global and local (India) sites, with important consequences for funding of health infrastructure, capacity, and training resources for addressing some of the existing structural inequalities. Dominant values currently defining point of care diagnostics risk exacerbating health inequalities between those who do and do not have the necessary social and financial resources to access better equipped and functioning healthcare facilities, especially in resource constrained settings.